Methodology for ensuring the functional stability of aircraft integrated modular avionics complex - Г. А. Калашник; М. А. Калашник-Рибалко (Наука і техніка Повітряних Сил Збройних Сил України)
The article presents the methodology of ensuring the functional stability of aircraft avionics complexes under the influence of failure and destabilizing factors. It is based on the procedure of maintaining valid knowledge bases of individual modules of the avionics complex through the organization of dynamic verification of such knowledge bases during their application on the principle of the probabilistic diagnostic core with system recovery without significant restructuring of verification means. The results of calculations of indicators of functional stability of the integrated avionics complex of the D-42 aircraft are presented in the article. To increase the efficiency of the integrated avionics complex under conditions of destabilizing influences, the optimal structure of the avionics complex of the D-42 aircraft was synthesized according to the criterion of the maximum indicator of functional stability with the limitation of the cost of construction the system. In the calculations, an increase in the generalized indicator of functional stability was achieved in comparison with the original structure by 30.8 % (from 294.2 to 384.9) for the given conditional cost 20,000 с.u. It is the most acceptable according to the generalized indicator of functional stability, as a criterion of preference under the specified cost limitations and taking into account the limitations of other parameters of the effective operation of the complex. Increasing the functional stability of the avionics complex according to the presented methodology will allow timely detection of implicit failures and parry their consequences. Based on the results of these studies there is a possibility: substantiation of requirements for the structures of avionics complexes to be designed, solving the problem of synthesis of optimal structure on the criterion of maximum functional stability with limited construction costs, as well as a reasonable increase in the structure of the distributed system of the aircraft avionics complex.